Organic Acids Regulation of Chemical–Microbial Phosphorus Transformations in Soils - Menezes-Blackburn, Daniel; Paredes, Cecilia; Zhang, Hao; Giles, Courtney D; Darch, Tegan; Stutter, Marc; George, Timothy S; Shand, Charles; Lumsdon, David; Cooper, Patricia; Wendler, Renate; Brown, Lawrie; et al. (Environmental science & technology, 2016)
We have used an integrated approach to study the mobility of inorganic phosphorus (P) from soil solid phase as well as the microbial biomass P and respiration at increasing doses of citric and oxalic acid in two different soils with contrasting agronomic P status. Citric or oxalic acids significantly increased soil solution P concentrations for doses over 2 mmol kg–1. However, low organic acid doses (<2 mmol kg–1) were associated with a steep increase in microbial biomass P, which was not seen for higher doses. In both soils, treatment with the tribasic citric acid led to a greater increase in soil solution P than the dibasic oxalic acid, likely due to the rapid degrading of oxalic acids in soils. After equilibration of soils with citric or oxalic acids, the adsorbed-to-solution distribution coefficient (K d) and desorption rate constants (k –1) decreased whereas an increase in the response time of solution P equilibration (T c) was observed. The extent of this effect was shown to be both soil and organic acid specific. Our results illustrate the critical thresholds of organic acid concentration necessary to mobilize sorbed and precipitated P, bringing new insight on how the exudation of organic acids regulate chemical–microbial soil phosphorus transformations.